Running a marathon from -45°C to +55°C in a climate chamber: a case study - Kälin, K.; Knechtle, B.; Rüst, C. A.; Mydlak, K.; Rosemann, T. (Open Access Journal of Sports Medicine, 2012)
Background: We describe a runner who completed a self-paced marathon (42.195 km) in a climate chamber with a temperature difference of 100°C, starting at an ambient temperature (Tambient) of -45°C and finishing at an Tambient of +55°C. Methods: Tambient was set at -45°C at the start, and was steadily increased at a rate of 1°C at 4.5-minute intervals to +55°C. Before the start, after every 10.5 km, and at the end of the marathon, body mass, urine, and sweat production were measured and samples of venous blood and urine were collected. The runner`s temperature was recorded every 10 seconds at four sites, ie, the rectum for body core temperature (Tcore), and at the forehead, right wrist, and right ankle for surface temperatures (Tskin). Results: The subject took 6.5 hours to complete the marathon, during which Tcore varied by 0.9°C (start 37.5°C, peak 38.4°C). The largest difference (Delta) of Tskin was recorded at the ankle (Delta 16°C). The calculated amount of sweat produced increased by 888% from baseline. In the blood samples, myoglobin (+250%) showed the highest change. Of the pituitary hormones, somatotropic hormone (+391%) and prolactin (+221%) increased the most. Regarding fluid regulation hormones, renin (+1145%) and aldosterone (+313%) showed the greatest increase. Conclusion: These results show that running a marathon in a climate chamber with a total DeltaTambient of 100°C is possible, and that the Tambient to Tcore relationship is maintained. These results may offer insight into regulatory mechanisms to avoid hypothermia and hyperthermia. The same study is to be performed using more subjects with the same characteristics to validate the present findings.